Influence of Organic Matter Vis-à-Vis Humic Acid on the Transformation of Inorganic and Organic Forms of Nitrogen in a Typic Haplustept Soil. Issue 9 (15th May 2017) - Devi, N. Surbala; Saha, D.
ABSTRACT: A laboratory experiment was conducted to study the changes in inorganic and organic forms of nitrogen (N) in a Typic Haplustept soil treated with mustard cake vis-à-vis humic acid in the presence and absence of inorganic N. Results revealed that irrespective of treatments, significantly higher amount of soluble nitrate (NO3 - ), hydrolysable ammonium (NH4 + ), non-hydrolysable and total N were accumulated in the soil treated with mustard cake in the presence of inorganic N. However, on the other hand, a humic acid-treated system showed significantly higher content of exchangeable NH4 + and hexosamine N. Application of humic acid alone leads to the accumulation of a significantly higher amount of total hydrolysable and unidentified N in the soil. Among the different treatments, NH4 + fixation was more in mustard cake followed by humic acid-treated soil. Humic acid is more susceptible to mineralization than mustard cake, particularly with respect to total N accumulation in soils.